Layer-by-layer assembled super-hydrophobic concrete coating and preparation method thereof
Through layer-by-layer assembly method, diluted PDMS and nano-laurate copper powder were sprayed on the concrete surface, which solved the problem of process complexity and roughness in the prior art, and achieved efficient preparation of superhydrophobic concrete coatings with good adhesion and corrosion resistance. layer.
Patent Information
- Application Number
- CN202411281833.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2024-12-27
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing superhydrophobic concrete coating preparation technology is complex, has high operation difficulty, and is not suitable for large-scale production. High-concentration PDMS spraying will cause the deterioration of nano-level surface roughness and affect the hydrophobic performance.
Using layer-by-layer assembly method, first spray diluted polydimethylsiloxane (PDMS) on the concrete surface to form a transparent thin liquid layer, and then cover nano copper laurate powder to form a superhydrophobic surface by drying and curing, using PDMS to Migration and electrostatic self-assemble micron-scale spherical aggregates, reducing solvent use and complex rough treatments.
It realizes a superhydrophobic coating with simple preparation, environmental protection, non-toxic and fast effect, with good adhesion, durability and corrosion resistance, and is suitable for large-scale production and application.
Smart Images

Figure CN119191879A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of building technology, and more specifically, to a super-hydrophobic concrete coating assembled layer by layer and a preparation method thereof. Background Art
[0002] As the most widely used and used building material in the world, the durability of concrete is directly related to the structural durability of the entire building. However, as concrete is a porous hydrophilic material, it often suffers from engineering problems such as deterioration and failure due to the invasion of external moisture during service, such as steel corrosion, freeze-thaw cycles, calcium dissolution, carbonization, and alkali-aggregate reaction, which seriously affect the strength and durability of concrete structures, and thus affect the service life and safety of the structure.
[0003] Based on this, the use of super-hydrophobic concrete coating can effectively block the path of external moisture entering the interior of the concrete, thereby improving the corrosion resistance and durability of the concrete structure. In order to achieve a super-hydrophobic concrete surface, a low surface energy water repellent is usually mixed with nanoparticles and attached to the concrete surface by coating or impregnation to construct a micro-nano structure, which has the advantages of simple operation, high controllability and environmental friendliness. However, the disclosed super-hydrophobic coating preparation technology generally has problems such as complex process, high difficulty in operation, and limited large-scale production capacity.
[0004] Chinese invention patent application CN 111944359 B discloses a method for preparing a micro-nano hierarchical super-hydrophobic coating by self-assembly of core-shell cellulose nanoparticles, which requires first synthesizing core-shell hydrophobic cellulose fatty acid ester nanoparticles, and then spraying a cellulose micro-nano particle suspension onto the substrate surface to prepare a coating with super-hydrophobic properties. The nanoparticle preparation process is cumbersome and requires multi-step reactions, which is not suitable for large-scale preparation and application.
[0005] Chinese invention patent application CN 117259164A discloses a long-acting solid super-hydrophobic nano gradient composite coating and its preparation method, the method presets high-strength binder (E-7 glue) bonding bottom by bottom composite technology, alternately sprays super-hydrophobic nano coating and PDMS to prepare composite coating twice, improves roughness while combining high-strength binder to achieve super-hydrophobic performance. Wherein high-concentration PDMS repeatedly sprays and can completely fill the nanostructure of hydrophobic particle construction, thereby deteriorating nanoscale surface roughness, and surface hydrophobicity and coating quality cannot be guaranteed. In addition, the method assembly process is complicated, and process is cumbersome, and is not suitable for large-scale preparation of super-hydrophobic coating. Summary of the invention
[0006] Based on the problems existing in the prior art, the present invention proposes a super-hydrophobic concrete coating assembled layer by layer and a preparation method thereof. The prepared super-hydrophobic coating has strong adhesion, and the preparation method has the advantages of convenient preparation, environmental protection, non-toxicity, and quick effect, providing support for the good application of super-hydrophobic materials in the field of building materials.
[0007] In order to achieve the above object, the technical solution of the present invention is as follows:
[0008] A super hydrophobic coating assembled layer by layer comprises a polydimethylsiloxane (PDMS) thin liquid layer arranged on a concrete surface and nano copper laurate powder covering the surface of the polydimethylsiloxane thin liquid layer.
[0009] Furthermore, the polydimethylsiloxane thin liquid layer is prepared by the following method:
[0010] Polydimethylsiloxane is dispersed in a low-polarity solvent to form a diluent, which is then sprayed on the concrete surface. After most of the low-polarity solvent evaporates at room temperature, a transparent thin liquid layer with a deposition thickness of 3-5 μm is formed.
[0011] Furthermore, the low polarity solvent includes any one of n-hexane, toluene, acetone and dichloromethane.
[0012] Specifically, the mass ratio of PDMS to the low polarity solvent in the diluent is 0.07-0.16:1.
[0013] In the present invention, the low-polarity solvent is used to dilute the PDMS, which can not only improve the curing efficiency of the PDMS, but also promote the migration of the PDMS to the surrounding of the nanoparticles.
[0014] Furthermore, the preparation method of the nano copper laurate powder is:
[0015] Lauric acid and copper hydroxide are added into a mixed solution of anhydrous ethanol and water, and the mixture is homogeneously dispersed at room temperature, and then dried to obtain nano copper laurate powder (with a particle size of 80-200 nm).
[0016] Furthermore, the mass ratio of lauric acid to copper hydroxide is 4-5:1, and the mass ratio of ethanol to water is 0.52-0.79:1.
[0017] The present invention provides a super-hydrophobic nano copper laurate prepared by a one-step method. On the one hand, the acid-base neutralization reaction rate of lauric acid and copper hydroxide can be increased by high-speed shearing; on the other hand, by regulating the ratio of ethanol-water, the competition between copper laurate and water for ethanol molecules is intensified, which triggers phase separation and induces copper laurate droplets to appear as nanometer-scale salt droplets.
[0018] A method for preparing the above-mentioned layer-by-layer assembled super-hydrophobic concrete coating comprises the following steps:
[0019] S1, dispersing polydimethylsiloxane in a low polarity solvent to form a diluent;
[0020] S2, spray the diluted liquid on the concrete surface, and let it dry and evaporate to form a transparent thin liquid layer;
[0021] S3, evenly covering the surface of the thin liquid layer with nano copper laurate powder, drying and solidifying, and removing the floating powder to obtain a super hydrophobic coating.
[0022] In step S1, the low polarity solvent includes any one of n-hexane, toluene, acetone and dichloromethane.
[0023] Furthermore, in step S1, the mass ratio of PDMS to low polarity solvent in the diluent is 0.08-0.15:1d
[0024] In step S2, the drying and curing temperature is room temperature to 80° C. In step S2, the first drying and curing is performed to volatilize the low-polarity solvent. There is no limit on the drying time, as long as the low-polarity solvent can be volatilized to form a transparent thin liquid layer.
[0025] In step S3, the drying and curing temperature is from room temperature to 80° C. There is no limit on the drying time, as long as it is completely cured. For example, it can be dried at 80° C. for 2 hours.
[0026] In the present invention, there is no restriction on the amount of the nano copper laurate powder, as long as it can be combined with PDMS.
[0027] In the present invention, the formation mechanism of the super-hydrophobic surface can be attributed to the migration of PDMS around the copper laurate particles. By covering the surface of the thin liquid layer of low surface energy PDMS with dried nano-copper laurate powder, the liquid PDMS will spontaneously migrate to the periphery of the copper laurate particles under the synergistic drive of capillary force and electrostatic force. In response to the flow of PDMS liquid, the nanoparticles will self-assemble into micron-scale spherical aggregates, thereby generating micro / nano synergistic roughness. The aggregation phenomenon of microparticles is suppressed due to the particle weight and steric hindrance, and will not cause the rough structure of the super-hydrophobic surface to deteriorate. After curing, a super-hydrophobic surface is obtained, and the static contact angle can reach more than 150°.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] (1) The present invention provides a layer-by-layer assembled super-hydrophobic concrete coating, which uses a low-concentration, uncured polydimethylsiloxane surface as an assembly substrate, sprays super-hydrophobic nano-copper laurate powder, and utilizes the interaction between nanoparticles and low-viscosity PDMS to promote the construction of coating surface roughness.
[0030] (2) The direct use of nano-copper laurate powder can reduce the use of solvents and eliminate the complex surface roughening steps, which is an economical and environmentally friendly method. Another advantage of using copper laurate powder is that the dispersibility of nanoparticles in PDMS-low polarity solvent during the layer-by-layer assembly process does not affect the preparation process and hydrophobic properties.
[0031] (3) After evaporating most of the low-polarity solvent at room temperature, a transparent thin liquid layer with a thickness of 3-5 microns is easily formed by gravity and self-leveling, and the coating thickness and quality are controllable. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to make the purpose, technical solution and beneficial effects of the present invention clearer, the present invention provides the following drawings for illustration:
[0033] Figure 1 The present invention is a flow chart of the preparation of super hydrophobic concrete coating in an embodiment;
[0034] Figure 2 This is a water drop morphology image of the surface of the super-hydrophobic concrete coating assembled layer by layer in Example 1;
[0035] Figure 3 This is a water drop morphology image of the surface of the hydrophobic concrete coating in Comparative Example 1;
[0036] Figure 4 Schematic diagram of adhesion performance test of super hydrophobic concrete coating assembled layer by layer in Example 1;
[0037] Among them, a is a schematic diagram of the tape test of the superhydrophobic concrete coating assembled layer by layer; b is a schematic diagram of the tape peeling of the superhydrophobic concrete coating assembled layer by layer. DETAILED DESCRIPTION
[0038] Many specific details are set forth in the following description to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited to the specific implementation disclosed below.
[0039] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0040] It should be noted that the raw materials, instruments, etc. involved in the present invention are all common commercially available products.
[0041] The present invention will be further described below in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present invention, and cannot be used to limit the protection scope of the present invention.
[0042] Example 1
[0043] The embodiment of the present invention provides a method for preparing a super-hydrophobic concrete coating assembled layer by layer, comprising:
[0044] (1) 8 g of lauric acid and 2 g of copper hydroxide are dispersed in a mixed solution of 31.6 g of anhydrous ethanol and 68.4 g of water, and then the mixture is homogenized and dispersed at room temperature for 1 hour, and finally dried to obtain nano copper laurate powder;
[0045] (2) dispersing 10 g of polydimethylsiloxane (PDMS) in 65.9 g of n-hexane to prepare a PDMS dilute solution;
[0046] (3) The diluted PDMS solution prepared in step (2) is uniformly sprayed on the concrete surface, and then placed in a vacuum drying oven to accelerate the volatilization of n-hexane to form a transparent thin liquid layer with a thickness of about 5 μm, and the nano-copper laurate powder prepared in step (1) is covered on the surface for 1 minute, and finally the excess powder is blown off and the prepared coating is cured in a vacuum drying oven at 80° C. for 2 hours to obtain a super hydrophobic concrete coating.
[0047] Example 2
[0048] The embodiment of the present invention provides a method for preparing a super-hydrophobic concrete coating assembled layer by layer, comprising:
[0049] (1) 8 g of lauric acid and 2 g of copper hydroxide are dispersed in a mixed solution of 39.5 g of anhydrous ethanol and 60.5 g of water, and then the mixture is homogenized and dispersed at room temperature for 1 hour, and finally dried to obtain nano copper laurate powder;
[0050] (2) dispersing 5 g of polydimethylsiloxane (PDMS) in 65.9 g of n-hexane to prepare a PDMS dilute solution;
[0051] (3) The diluted PDMS solution prepared in step (2) is uniformly sprayed on the concrete surface, and then placed in a vacuum drying oven to accelerate the volatilization of n-hexane to form a transparent thin liquid layer with a thickness of about 4 μm, and the nano-copper laurate powder prepared in step (1) is covered on the surface for 1 minute, and finally the excess powder is blown off and the prepared coating is cured in a vacuum drying oven at 80° C. for 2 hours to obtain a super hydrophobic concrete coating.
[0052] Example 3
[0053] The embodiment of the present invention provides a method for preparing a super-hydrophobic concrete coating assembled layer by layer, comprising:
[0054] (1) dispersing 10 g of lauric acid and 2 g of copper hydroxide in a mixed solution of 39.5 g of anhydrous ethanol and 60.5 g of water, and then homogenizing and dispersing the mixture at room temperature for 1 hour, and finally drying the mixture to obtain nano copper laurate powder;
[0055] (2) dispersing 10 g of polydimethylsiloxane (PDMS) in 65.9 g of n-hexane to prepare a PDMS dilute solution;
[0056] (3) The diluted PDMS solution prepared in step (2) is uniformly sprayed on the concrete surface, and then placed in a vacuum drying oven to accelerate the volatilization of n-hexane to form a transparent thin liquid layer with a thickness of about 3 μm, and the nano-copper laurate powder prepared in step (1) is covered on the surface for 1 minute, and finally the excess powder is blown off and the prepared coating is cured in a vacuum drying oven at 80° C. for 2 hours to obtain a super hydrophobic concrete coating.
[0057] Example 4
[0058] The embodiment of the present invention provides a method for preparing a super-hydrophobic concrete coating assembled layer by layer, comprising:
[0059] (1) dispersing 10 g of polydimethylsiloxane (PDMS) in 65.9 g of toluene to prepare a PDMS dilute solution;
[0060] (2) The diluted PDMS solution prepared in step (1) was uniformly sprayed on the concrete surface, and then placed in a vacuum drying oven to accelerate the volatilization of n-hexane to form a transparent thin liquid layer with a thickness of about 5 μm, and commercially available copper laurate powder (Xinji Anhaiwei Biotechnology Co., Ltd.) was covered on the surface for 1 minute, and finally the excess powder was blown off and the prepared coating was cured at room temperature for 8 hours to obtain a superhydrophobic concrete coating.
[0061] Comparative Example 1
[0062] Based on Example 1, step (3) is specifically as follows:
[0063] The nano copper laurate powder prepared in step (1) is dispersed in a PDMS dilution solution, sprayed evenly on the concrete surface, and dried and cured in a vacuum drying oven at 80° C. for 2 hours to obtain a super hydrophobic concrete coating.
[0064] The contact angle and hardness tests were performed on the concrete hydrophobic coatings prepared in Examples 1-3 and Comparative Example 1. The results are shown in Table 1.
[0065] Table 1 Contact angle and hardness test
[0066]
[0067] Next, the super-hydrophobic concrete coating prepared in Example 1 was subjected to an adhesion test, i.e., a tape peeling test. The results are as follows: Figure 4 As shown, there is no trace of the super-hydrophobic concrete coating assembled layer by layer falling off on the surface of the 3M tape, and the super-hydrophobic concrete coating assembled layer by layer is still well attached to the concrete substrate, which shows that the super-hydrophobic concrete coating assembled layer by layer has good adhesion to the concrete substrate. Finally, the layer-by-layer assembled super-hydrophobic concrete coating prepared in Example 1 was subjected to a durability performance test. The coating was subjected to multiple physical damages, such as 60 cycles of tape peeling or 80 cycles of friction, and the coating still had super-hydrophobic properties; whether it was soaked in 3.5wt% NaCl salt water for one hour or soaked in a solution with a pH of 2 to 12 for one hour, the super-hydrophobic coating can still maintain good super-hydrophobicity, and the contact angle CA>150°, as shown in Table 2.
[0068] Table 2 Contact angle test in different pH solutions
[0069]
[0070] Based on the above test results, the following conclusions can be drawn: the present invention simply prepares a super-hydrophobic coating with good physical and chemical properties by homemade nano copper laurate powder and layer-by-layer assembly, and the contact angle of the prepared layer-by-layer assembled super-hydrophobic concrete coating is greater than 150 °, with good hydrophobic properties. At the same time, after the tape stripping test, the coating did not fall off. In addition, after 80 cycles of sandpaper friction, the coating still has hydrophobicity. In addition, even in a strong electrolyte environment, the super-hydrophobic concrete coating still has good super-hydrophobicity, and its good corrosion resistance can better protect the substrate.
[0071] It can be seen that the layer-by-layer assembled super-hydrophobic concrete coating prepared by the present invention has good adhesion, durability and corrosion resistance, which provides great possibilities for large-scale production applications.
[0072] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A super-hydrophobic concrete coating assembled layer by layer, characterized in that: The invention comprises a polydimethylsiloxane thin liquid layer arranged on the surface of concrete and nano copper laurate powder covering the surface of the polydimethylsiloxane thin liquid layer.
2. The super-hydrophobic concrete coating assembled layer by layer according to claim 1, characterized in that: The polydimethylsiloxane thin liquid layer is prepared by the following method: Take polydimethylsiloxane and disperse it in a low-polarity solvent to form a diluent, spray it on the concrete surface, and dry and solidify to obtain the product.
3. The super-hydrophobic concrete coating assembled layer by layer according to claim 2, characterized in that: The low polarity solvent includes any one of n-hexane, toluene, acetone and dichloromethane.
4. The super-hydrophobic concrete coating assembled layer by layer according to claim 2, characterized in that: The mass ratio of PDMS to the low polarity solvent in the diluent is 0.07-0.16:
1.
5. The layer-by-layer assembled super-hydrophobic concrete coating according to claim 1, characterized in that: The preparation method of the nano copper laurate powder is: The lauric acid and copper hydroxide are dispersed in a mixed solution of anhydrous ethanol and water, and the mixture is homogeneously dispersed at room temperature, and then dried to obtain nano copper laurate powder.
6. The layer-by-layer assembled super-hydrophobic concrete coating according to claim 5, characterized in that: The mass ratio of lauric acid to copper hydroxide is 4-5:1, and the mass ratio of ethanol to water is 0.52-0.79:
1.
7. A method for preparing a layer-by-layer assembled super-hydrophobic concrete coating according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1, dispersing polydimethylsiloxane in a low polarity solvent to form a diluent; S2, spraying the diluted liquid on the concrete surface, drying and solidifying to form a thin liquid layer; S3, evenly covering the surface of the thin liquid layer with nano copper laurate powder, drying and solidifying, and removing the floating powder to obtain a super hydrophobic coating.
8. The preparation method according to claim 7, characterized in that: In step S1, the low polarity solvent includes any one of n-hexane, toluene, acetone and dichloromethane; the mass ratio of PDMS to the low polarity solvent in the diluent is 0.07-0.16:1d.
9. The preparation method according to claim 7, characterized in that: In step S2, the drying and curing temperature is from room temperature to 80°C.
10. The preparation method according to claim 7, characterized in that: In step S3, the drying and curing temperature is from room temperature to 80°C.
Citation Information
Patent Citations
Preparation method of SiO2 / PDMS composite transparent super hydrophobic coating
CN105694715A
Method for forming superhydrophobic coating layer using PDMS and micropowders
KR101871073B1
